Inter-religious dialogue: detrimental to aqidah or medium of da'awah - Ab. Majid, Arfah (Human Resource Management Academic Research Society, 2022)
The implementation of inter-religious dialogue in Malaysia is still less encouraging, although it has been implemented for a few decades. This reality is apparently associated with scepticism towards inter-religious dialogue itself. Inter-religious dialogue is often misunderstood as a platform to promote religious pluralism which is detrimental to aqidah. However, a case study conducted on three Islamic organizations namely Islamic Propagation Society International (IPSI), Institut Kefahaman Islam Malaysia (IKIM) and Islamic Information Services (IIS) conveyed that these organizations had implemented inter-religious dialogue as part of their da’wah efforts. This study aims at exploring the implementation of inter-religious dialogue in Malaysia, assessing the role of inter-religious dialogue in da’wah as stated in the Quran and, examining Islamic organizations involve in inter-religious dialogue and da’wah. This study offers a novelty in the realm of inter-religious dialogue where it combines socio-psychological and theological framework in gauging inter-religious dialogue in Malaysia. The findings from this study yields practical implication for the dialogue practitioners and organizations to enrich their own dialogue models based on the types and designs of dialogue identified in this research. The findings also proves that dialogue is harmless to aqidah, in fact it is a medium to spread da’wah.